Aplicación móvil bajo plataforma Android para la gestión de pedidos y control de rutas de los distribuidores de gas licuado de petróleo GLP en la ciudad de Guaranda, año 2019 - Rochina Rochina, Diego Moises (2019)
This research project was carried out of the LPG "Distributor Hnos Caraballo", with the development of a multiplatform mobile application called G-MIGAS for Android and IOS that will facilitate the product delivery processes to the final consumer through vehicle routes, that is, the management and orders and route control, for this, the problem, objectives, justification and scope that the application will cover were raised. As a first section, it encompasses the theoretical framework where the different definitions discussed in this section are developed, all based on updated bibliographic sources, key issues such as market research, sales processes, hybrid mobile applications, web service, framework, geolocation with Open Street Maps The second section describes the different methodologies applied in the research, techniques and instruments for the collection of the information required in the development of this work and information processing, carried out with the purpose of complying with the objectives set. For the third section, software engineering was applied in a more technical way for the development of the system to be implemented from the administration to the final client, summarizing, as tools used Ionic Framework, Angular, REST API, PHP, PostgreSQL, hosting , domain, Android Studio, etc. the methodology used Mobile-D in all its phases, user history, functional and non-functional requirements, diagrams, data dictionary, interface development, economic feasibility, all this will generate ERS documents, DDS, test plan, manual of user. Finally, the development as part of the market study is attached, a CANVAS business model is presented, where the current status of the distributor is presented, thus, proposing some market strategies with the objective of generating greater distribution of its product among consumers. Keywords: G-MIGAS, Ionic Framework, Angular, API REST, PHP, PostgreSQL Hosting, Dominio, CANVAS.